MALDI-TOF MS in Adult Inpatients with Bloodstream Infections: Pre- and Post-intervention Study. (4th October 2017) - Khan, Salman; Dunn, Dallas; Patel, Gargi; Saunders-Hao, Patricia; Rana, Meenakshi; Patel, Gopi; Hamula, Camille
Abstract: Background: Delays in diagnosis of bloodstream infections (BSI) can lead to adverse outcomes. Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) can rapidly identify bacteria directly from blood culture bottles. We describe our experience in patients with BSI before and after implementation of MALDI-TOF MS. Methods: Patients: adult inpatients with BSI. Design: pre-intervention group (August-November 2015); bacterial identification and susceptibility testing performed by Vitek®2. Post-intervention group (August–November 2016); bacterial identification on liquid blood culture broth by MALDI-TOF MS; susceptibility testing performed by Vitek®2. Both groups received baseline antimicrobial stewardship program (ASP) intervention. Outcomes: times to bacterial identification, susceptibilities, effective and optimal antibiotics, length of stay (LOS), 30-day readmission and 30-day all-cause mortality. Statistical analysis: univariable analysis performed; continuous variables analyzed using a two-tailed t-test; discrete variables analyzed using a chi-square test or Fisher exact test. Results: 267 cases of BSI occurring in 256 patients were analyzed (137 pre-intervention, 130 post-intervention). Time to bacterial identification was significantly shorter in the MALDI-TOF MS group (40 vs. 63 hours, P < 0.001). Times to susceptibilities, effective, and optimal antibiotic therapy did not differ between the two groups. There was no significant difference in LOS or 30-day readmission rates. 30-day mortality was significantly higher in the pre-intervention group (25 vs. 13 percent, P = 0.026). The pre-intervention group had significantly more BSI due to multidrug-resistant (MDR) Gram-negative bacteria and vancomycin-resistant enterococci (VRE). Conclusion: MALDI-TOF MS significantly shortened time to bacterial identification in patients with BSI. Differences in times to effective and optimal antibiotic therapy were not observed. This may be due to high rates of early appropriate empiric antibiotic use at our institution and limited real-time MALDI-TOF MS and ASP interventions. Higher mortality in the pre-intervention group may be due to higher prevalence of multidrug-resistant bacteria. Disclosures: All authors: No reported disclosures.